D-Dimer Sebagai Salah Satu Parameter Perbaikan Klinis pada Kasus Covid-19 Gejala Berat - Trilaksmi, Antin; Martin (Universitas Muhammadiyah Prof. Dr. Hamka (UHAMKA Press), 2022)
Background. Coronavirus Disease 2019 (COVID-19) has been a global pandemic since March 2020. The number of patients is massive and clinical symptoms vary from mild to severe symptoms. Several laboratory results showed abnormal values in Covid-19 patients, including an increase in the value of D-dimer. Elevated levels of D-dimer in COVID-19 patients are strongly associated with severity and increased mortality. We report a case of a severe symptomatic COVID-19 patient with high D dimer levels at the start of treatment and showing clinical improvement according to a decrease in D dimer levels. Methods. We treat and follow the clinical and laboratory developments of COVID-19 patients with severe symptoms from the time they enter the Intensive Care Unit (ICU) until they move to a regular ward. Results. A 53-year-old male patient diagnosed with viral pneumonia et causa covid-19 was admitted to the ICU with severe symptoms and high initial d-dimer levels (1,413 ug/ml). The patient received ventilator assistance and standard therapy according to the Covid 19 management protocol of the Ministry of Health of the Republic of Indonesia. Anticoagulation using heparin intravenously with a dose adjusted to the level of d dimer, aPTT, and clinical condition of the patient who is monitored regularly. The trend of d dimers decreased parallel to the decrease in C reactive protein (CRP) levels, increased lung gas exchange function was evaluated from the PaO2/Fio2 ratio (PF ratio) and the clinical improvement of the patients. Conclusion. D-dimer is closely related to the severity of covid 19 patients. D dimer can be used as one of the parameters of patient clinical improvement.